Adequacy of Data on Injuries' External Causes for Coding Based on ICD-10 in Inpatient Medical Records and Emergency Wards of Shahid Beheshti Hospital in Kashan - Fatemeh Rangraz Jeddi; Mohammad Reza Rezayi Mofrad; Maryam Rangraz Jeddi (Tehran University of Medical Sciences, 2012)
Background and Aim: Knowledge about the external causes of accidents is vital for their prevention, and insufficient data on external causes can reduce their usefulness. That is why, the adequacy of the sources of data is of great importance. The aim of this research is to study the adequacy of data regarding the injuries external causes for coding based on ICD-10 in inpatient medical records and emergency wards of Kashan Shahid Beheshti Hospital.Materials and Methods: This prospective descriptive cross-sectional research was done on 1000 patients in Kashan Shahid Beheshti Hospital in 1386 (2007). The data needed for coding were chosen from medical records based on ICD-10 rules and for the following groups: transportation accidents, poisoning, burns, lightning, assaults, respiratory threats, intentional self harm, contact with venomous animals, and exposure to animate and inanimate mechanical forces. Then, the data were put in a checklist and analyzed with SPSS and descriptive statistics. Results: The data required for the three main characters of the external causes of injuries were adequate in 740 files (47%); the figure for the fourth character of the external causes of transportation accidents was found to be 430 (88.7%). Figures for the place of occurrence and the type of subjects activities at the time of accidents were found to be sufficient in 109 cases (21.16%) and 50 cases (5%), respectively. Conclusion: Data on the eternal causes of injuries do not have the required adequacy. More evaluations are essential to enhance the adequacy of such data.